(untitled) (Economics and region, 2025)
Innovative development of enterprises involves the purposeful creation, implementation and diffusion of new technologies, management solutions, business models and organizational forms that provide the enterprise with the ability to adapt, increase competitiveness and form long-term strategic advantages. It covers complex transformations of production, logistics, financial, marketing and management processes, based on the active use of knowledge, digital technologies, intellectual capital and innovative practices. The essence of innovative development is the transition of the enterprise to a higher level of organizational dynamics, when changes become continuous, controlled and strategically oriented. The work systematizes and generalizes scientific approaches to modeling innovative management of enterprise development. A comprehensive system of models has been formed, covering various trajectories of organizational development: evolutionary, revolutionary, structural-situational, innovative, selection, phenomenological, conflict, entrepreneurial, Carnegie model, mass service model, as well as modern models - "open innovation", "triple helix", Kaizen, Lean, Agile, digital transformation, diffusion of innovations, innovation life cycle (S-curve), BSC, innovation ecosystem, "blue ocean", venture investment and innovation maturity model. It is shown that the innovative development of enterprises is a multidimensional process that covers structural, behavioral, socio-economic and technological aspects of transformation, and the models serve as tools for assessing the driving forces of change, choosing strategies and managing innovation processes. The proposed systematization of models allows determining the level of innovation maturity of an enterprise, forming effective development strategies and increasing the effectiveness of management decisions. The results of the study can be used to form innovative development strategies, improve corporate governance systems, prepare digital transformation programs, implement innovative management methods and increase the competitiveness of enterprises in a dynamic market environment.